The Last Visits of the Abbots of Valladolid to the Priory of San Salvador de Chantada (Lugo): Edition and Study - Méndez Pérez, Xosé (Madrygal. Revista de Estudios Gallegos, 2016)
Bearing in mind the general crisis of the 14th and 15th centuries, this work studies the impact of the reformation initiated by San Benito el Real de Valladolid and the consequent dependence of all the reformed monasteries to this house. In this work we shall concentrate on four monastic visits in the last years of the Priory of San Salvador de Chantada, Lugo, before the Ecclesiastical Confiscations took place. Transcriptions of these visits can be found in the appendix.